Nitrogen and sulfur fertilizers promote the absorption of lead and cadmium with Salix integra Thunb. by increasing the bioavailability of heavy metals and regulating rhizosphere microbes - Wang, Shaokun; Niu, Xiaoyun; Di, Dongliu; Huang, Dazhuang (Frontiers in Microbiology, 2022)
Fertilization is an effective agronomic strategy to improve the efficiency of phytoextraction by Salix integra Thunb. However, the specific effects of the simultaneous application of nitrogen (N) and sulfur (S) fertilizers in the rhizosphere remain unclear. We investigated the bioavailability of lead (Pb) and Cadmium (Cd) along with the microbial metabolic functions and community structure in the rhizosphere soil of S. integra after the application of N (0, 100, and 200 kg·ha-1·year-1) and S (0, 100, and 200 kg·ha-1·year-1) fertilizers for 180 d. The simultaneous application of N and S fertilizers significantly enhanced the absorption of Pb and Cd by S. integra, whereas this effect was not observed for the single application of N or S fertilizer. The contents of acid-soluble Pb and Cd in the rhizosphere soil significantly increased after either single or combined fertilize applications. The microbial metabolic activity was enhanced by the N and S fertilizers, whereas the microbial diversity markedly decreased. The metabolic patterns were mainly affected by the concentration of N fertilizer. The dominant fungi and bacteria were similar under each treatment, although the relative abundances of the dominant and special species differed. Compared to the N200S100 and N200S200 treatments, the N100S100 and N100S200 treatments resulted in fewer pathogenic fungi and more rhizosphere growth-promoting bacteria, which promoted phytoremediation by S. integra. Redundancy analysis indicated that the pH and nitrate content were the key factors affecting the structure of the microbial community. Collectively, the results suggest interactive effects between N and S fertilizers on the rhizosphere soil, providing a potential strategy for plant-microbial remediation by S. integra.